Burden and posttraumatic growth in adult caregivers of cancer patients - Teixeira, Ricardo João (2020)
Caring for someone with cancer can be a traumatic experience since the cancer diagnosis can lead to a significant amount of distress not only for the patients but also for their caregivers. Indeed, many studies have shown that caregivers of patients with cancer can experience higher levels of anxiety, depression and poor quality of life, and that these levels are equal or even greater than those found in patients. Nevertheless, more recently, studies have also shown that not only patients, but also their caregivers are able to experience positive changes in their lives as a result of this traumatic event. In this chapter, we aimed to characterize a sample of adult caregivers of patients with cancer by examining (1) the associations between caregivers’ sociodemographic (gender) and patients’ clinical variables (length of patients’ disease and treatment as well as the level of patients’ dependency) and psychological variables (caregiving burden and posttraumatic growth), and (2) the associations between burden and posttraumatic growth. Participants were 214 adult children caregivers of parents with cancer (74% women; Mean age = 33.12; SD = 9.15), and completed a Sociodemographic and Clinical Questionnaire, the Burden Assessment Scale, and the Posttraumatic Growth Inventory. Overall, disrupted activities were associated with a greater appreciation of life, guilt and burden were associated with more changes in relating to others. Moreover, women caregivers who reported to provide care for less than 1 a year, whose parents’ disease duration was less than 1 year, and those who perceived their parent as completely dependent on their caregiving experienced more burden but also more posttraumatic growth. These exploratory findings suggest that caregivers may experience burden when they care for a relative with cancer, but they are also able to experience growth, especially in the way they relate with others and appreciate life. Moreover, the results may help to identify caregivers who are at greater risk for developing burden or may have more difficulties in experiencing growth and for this reason are likely to benefit more from psychosocial interventions.